On the dependence of Ionic conductivity of ScSZ electrolytes on temperature of their sintering - Kyrpa, O.; Vasylyev, O.; Brychevs’kyi, M.; Pryshchepa, E.; Smirnova, A. (Видавництво Львівської політехніки, 2012)
The dependencies of ionic oxygen conductivity of 10Sc1CeSZ electrolytes made of different zirconia powders those differ by their impurities and production technologies, and sintered in air at different temperatures after uniaxial pressing are analyzed in terms of their Arrhenius equations in 400-900oC temperature range. Deviation from a typical linear dependence of conductivity on temperature that is the most clearly visible in the electrolyte made of the purest powder is observed as a kink on the temperature dependency. A position of the kink point is determined by powder properties and is practically independent on temperature of powder sintering.
Keywords: 10Sc1CeSZ powder; ScSZ electrolyte; oxygen ionic conductivity; conductivity temperature dependence; sintering